Decarbonylative cascade cyclization of ortho-cyanoarylacrylamides with pivaldehyde: Access to tert-butyl containing quinolone-2, 4(1H, 3H)-diones. (1st January 2022) - Zhang, Cui; Xia, Wen-Jin; Fan, Tai-Gang; Ding, Xue-Ling; Li, Ya-Min
Abstract: A TBPB initiated decarbonylative cascade cyclization of ortho -cyanoarylacrylamides with pivaldehyde leads to tert -butyl containing quinolone-2, 4(1 H, 3 H )-diones by formation of both C(sp 3 )–C(sp 3 ) and C(sp 3 )–C(sp 2 ) bonds. The reaction features simple reaction conditions and convenient reagents. Two radical additions are involved in the transformation. Graphical abstract: Image 1